Merck and Vioxx: An Examination of an Ethical Decision-Making Model - Cavusgil, Erin (Journal of business ethics, 2007)
Marketing researchers have proposed various conceptual models of ethical decision-making to better clarify the steps in the decision-making process. However, lacking in the literature is comprehensive empirical validation of these models. This manuscript examines the ethical decision-making model proposed by␣Ferrell et al. [1989, Journal of Macromarketing 56(Fall), 55–64] in the context of a real-world marketing situation. This model is a comprehensive synthesis of previously developed models in the literature. The events surrounding the withdrawal from the market of the pain reliever Vioxx, manufactured by Merck & Co., are detailed. The analysis provides insights into the decision-making process faced by Merck executives and sheds light onto the real-world applicability of the conceptual model. Furthermore, this study demonstrates how potential modifications to existing models can be developed by their examination in the context of real world events. It is hoped that this analysis, along with future examinations, aids marketing researchers in developing a better understanding of the ethical decision-making process in a business context.